Systems-biology dissection of mechanisms and chemical basis of herbal formula in treating chronic myocardial ischemia. (December 2016) - Guo, Shuzhen; Li, Peng; Fu, Bangze; Chuo, Wenjing; Gao, Kuo; Zhang, Wuxia; Wang, Junyao; Chen, Jianxin; Wang, Wei
Abstract: Herbal medicine is a mixture of multiple compounds, and is intended to exhibit therapeutic effects by attacking multiple disease-causing modules simultaneously. However, it is still a challenge for scientists to untangle the complex biological mechanisms and underlying material basis of herbal medicine. Here, this study was designed to build a systems-biology platform for exploring the molecular mechanisms and corresponding active compounds, with a typical example applied to an herbal formula Qishenkel (QSKL) in the treatment of chronic myocardial ischemia. We have applied an approach integrating transcriptome sequencing, bioactivity profiling inference, computational ligand-receptor evaluation and experimental validation to study the effects on pig myocardial ischemia treated with QSKL. Numerous biological modules were revealed and indicated the coordinated regulation of molecular networks from various aspects of cardiac function. In addition, gene expression profiles were utilized to identify a number of key therapeutic targets of herbal formula, such as angiotensin-converting enzyme and calcium channels. Then, these therapeutic targets were used to fish the potential active ingredients based on a combination of target structure-based and chemical ligand-based methods. Some active compounds, including luteolin, cryptotanshinone, licochalcone A, glycyrrhetinic acid, salsolinol, isoacid chlorogenic C, salvianolic acid A and salvianolic acid B, have been validated by direct biochemical methods. This strategy integrating different types of technologies is expected to provide not only a detailed understanding about the combined therapeutic effects of herbal mixture but also a new opportunity for discovering novel natural molecules with pharmacological activities.